The hello, goodbye window - Juster, Norton 1929-; Raschka, Christopher (New York Michael di Capua Books/Hyperion Books for Children, 2005)
Looking through the kitchen window, a little girl and her doting grandparents watch stars, play games, and, most importantly, say hello and goodbye.
Caldecott Medal, 2006.
Keywords: Grandparent and child -- Fiction; Windows -- Fiction